2020
DOI: 10.1128/mra.00301-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Five Salmonella enterica Phages, NBSal001, NBSal002, NBSal003, NBSal004, and NBSal005

Abstract: Salmonella enterica is a Gram-negative bacterium, recognized as one of the most important foodborne pathogens in the world. Bacteriophages represent a promising alternative to the biocontrol of Salmonella. Here, we report the isolation of five Salmonella bacteriophages, the sequencing of their full genomes, and initial genomic characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The sequencing and assembly quality data indicated that MinION data alone, with Racon assembly, gave the best results and identified the most coding sequences. Although, no major differences were detected between the different assemblies and the reference Salmonella phage S131 [ 51 ]. However, it could be that the pipeline used for hybrid assembly in this study needs to be improved because this pipeline is optimized for bacteria and not phages.…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing and assembly quality data indicated that MinION data alone, with Racon assembly, gave the best results and identified the most coding sequences. Although, no major differences were detected between the different assemblies and the reference Salmonella phage S131 [ 51 ]. However, it could be that the pipeline used for hybrid assembly in this study needs to be improved because this pipeline is optimized for bacteria and not phages.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bacteriophages for the control of Salmonella enterica colonization in the poultry industry is an alternative to reduce this prevalence. We report the complete genome sequences of two lytic Salmonella bacteriophages that are related to NBSal001, which was described previously; for this reason, we named Salmonella phages F115 and F61 NBSal001-like ( 1 ).…”
Section: Announcementmentioning
confidence: 99%
“…Phage genomic DNA was extracted using a modified phenol-chloroform method, including a DNase step to limit bacterial DNA contamination ( 4 ). The QIAseq FX single-cell DNA library kit was used to prepare the genomic library, followed by sequencing on the MiSeq Illumina platform (151-bp paired-end reads).…”
Section: Announcementmentioning
confidence: 99%